Implementation of the civil service competency model in Lithuania - Liukinevičienė, Laima (Univerzita Pardubice, 2017)
The article presents summarized results of a survey of the New Civil Service Competency Model which has been implemented in the Republic of Lithuania since 2013. The survey focuses on the implementation process. The study was intended to determine the responsibilities of the state and municipal and other organizations while implementing the Model as well as the purposefulness of its development. The benefit of the Model implementation for the entire public administration system, on the one hand, and an individual institution, on the other, was granted by thorough analysis of relevant scientific literature including the investigation of proper national and institutional (municipal) documents. The purpose was to find out whether separate institutions must be involved in the Model implementation and what factual measures they had to be responsible for. The results of the survey showed that separate institutions were actively involved in the personnel recruitment and training processes through implementing the Civil Service Competency Model (hereinafter CSCM, the Model), and the organizations were undergoing structural changes aiming at HR management improvement. The following directions of the institutional process improvement were suggested by the study: to increase the wider perception of the Model opportunities; to activate its use and application in such processes as personnel planning, assessment and other.
Keywords: public administration; modernization; civil service; human resources; CSCM; municipal institutions; O15; H11